PELAKSANAAN PENYULUHAN HIPERTENSI DESA TAMALATE, KECAMATAN GALESONG UTARA, KABUPATEN TAKALAR TAHUN 2022 - Handayani Meliana; Jayadilaga Yadi; Istiqamah Nurul Fajriah (Universitas Pahlawan Tuanku Tambusai, 2022)
Hypertension or high blood pressure is a disease that is a health problem throughout the world, specifically Indonesia. The purpose of this action is to overcome the problem of hypertension in Tamalate Village, Galesong District, Takalar Regency, which are the 3 main health problems in the area. The method used was giving counseling, distributing posters related to hypertension, carrying out pre-post tests and physical interventions, namely giving watermelon juice during counseling. This activity was carried out in Tamalate Village involving 4 hamlets namely Soreang, Bontotangnga, Tamalate and Soreang Baru hamlets. There were 40 residents of Tamalete Village who were involved in the activity. Analysis of the data that has been collected using SPSS 20 by comparing the pre-test and post-test scores on the respondents. The results of data analysis showed that there was an increase in the amount of knowledge of 40 respondents before counseling with high knowledge after evaluating hypertension counseling, from 44.1% to 85.6%. Meanwhile, the number of respondents who had less knowledge decreased from 55.9% to 14.4% after evaluating hypertension counseling. Keywords: Counseling, Hypertension, Watermelon and hypertension